Peran Cost-Benefit Analysis, Short-Term Resource Allocation, dan Operational Flexibility terhadap Efektivitas Pengambilan Keputusan Taktis - Feronika Arfianingrum; Yeni Kartika Dewi Nurjana; Lidh Iatul Izzah; Novita Melliyana Widyanti; Lebrina Lorince Tangpen; Elsy Margaritha Prastisye Rihi; Hwihanus Hwihanus; Maria Yovita R Pandin (ManBiz: Journal of Management and Business, 2025)
The current competitive and dynamic business era, encourages companies to be able to adapt and be able to make decisions quickly and appropriately. Short-term tactical decision making plays an important role in the company in maintaining the sustainability, profitability, and competitiveness of the company. In making tactical decisions, the integration between Cost-Benefit Analysis (CBA), Short-Term Resource Allocation (STRA), and Operational Flexibility (OF) plays an important role the purpose of this study to determine the role of Cost-Benefit Analysis, Short-Term Resource Allocation, and Operational Flexibility to the effectiveness of tactical decision making. This study comprehensively discusses how Cost-Benefit Analysis (CBA), Short-Term Resource Allocation (STRA), and Operational Flexibility (OF) work as three main pillars that complement each other in determining the quality of a company's tactical decisions. The CBA is tasked with evaluating financial viability through benchmarking relevant costs and benefits; the STRA ensures limited resources are allocated effectively according to priorities; while OF provides adaptability so that tactical decisions can be applied flexibly despite sudden changes in the business environment. The integration of the three concepts creates rational, efficient and adaptive tactical decisions. This study uses qualitative research methods with literature review approach.